The benefits and challenges of taxing sugar in a small island state: an interrupted time series analysis - Alexa Blair Segal; Jack Olney; Kelsey K. Case; Franco Sassi (BMC, 2022)
Abstract Background Beverage and food taxes have become a popular 'best buy' public health intervention in the global battle to tackle noncommunicable diseases. Though many countries have introduced taxes, mainly targeting products containing sugar, there is great heterogeneity in tax design. For taxes levied as import tariffs, there is limited evidence of effectiveness in changing the price and sale of taxed products, while the evidence base is stronger for excise taxes levied as a fixed amount per quantity of product. This paper examines the effect of the Bermuda Discretionary Foods Tax, which was based on import tariff changes, on retail prices and sales of sugar-sweetened beverages (SSBs), and on selected fruits and vegetables that benefited from a tariff reduction. Methods We used weekly electronic point-of-sale data from a major food retailer in Bermuda. We assessed historical weekly sales and price data using an interrupted time series design on 2,703 unique products between the dates of January 2018 through January 2020, covering 103 weeks. Results By January 2020, the average price per ounce of SSBs increased by 26.0%, while the price of untaxed beverages (including waters and non-added sugar drinks) remained constant. The increasing price of SSBs was the sole observable structural driver of SSB market share, responsible for a decrease in the market share by nearly eight percentage points by the end of the study period. The subsidy on fruits and vegetables was ineffective in changing prices and sales, due to the relatively small 5% import tax decrease. Conclusions The tax was largely passed through to consumers. However, several factors mitigated the impact of the tax on the prices paid for SSBs by consumers, including the specific design of the tax, price promotions and consumer responses. The experience of Bermuda provides important lessons for the planning of similar taxes in the future.